Kinetics of geopolymer's solidification: Effect of concentrations and curing temperatures. Issue 1 (May 2020) - Aman,; Awaluddin, A; Ahmad, A; Olivia, M; Herman, S; Fermi, MI
Abstract: This paper report the experimental study on the kinetic of geopolymer's solidification by determining setting time by varying activator concentrations of 10 M, 12 M, 14 M and 16 M, and curing temperatures of 30, 60, 80 and 100°C. However prior to the study of the effect the feasiblity of equipment using Vicat Needle. The transformation process of geopolymer crystal formation is analyzed by Avrami's kinetica theory. From the results of the experimental showed the increase activator concentration and curing temperature produce shorter setiing time for geopolymer's solidification. From the Avrami kinetic teory's the growth form of crystal in the geopolymerization showed constant (K) of particle growth is 5.42 × 10-2 and the value of Avrami's component n = 2.310 so that it can be concluded from the perspective of Avrami's kinetic theory, the rate of crystal growth solidification in this geopolymerization process shows a two-dimensional structure.